Are respectful maternity care (RMC) interventions effective in reducing intrapartum mistreatment against adolescents? A systematic review - Habib, Helen H.; Mwaisaka, Jefferson; Torpey, Kwasi; Maya, Ernest Tei; Ankomah, Augustine (Frontiers in Global Women's Health, 2023)
Intrapartum mistreatment of women by health professionals is a widespread global public health challenge. It leads to a decreased quality of maternity care and is evinced to precipitate detrimental maternal and neonatal outcomes, especially among adolescents. Relatedly, studies have suggested that Respectful Maternity Care (RMC) interventions are especially effective in mitigating intrapartum mistreatment and improving birth outcomes. However, evidence on the success of RMC, specifically for adolescents, is insufficient and unaggregated. Accordingly, the specific aim of this study is to synthesize the available evidence relating to the provision of RMC for parturient adolescents. This review searched for relevant literature from published and gray sources including PubMed, ScienceDirect, Cochrane, CINAHL, PsycINFO, Scopus, as well as Population Council, WHO and White Ribbon Alliance data sources published between January 1990 and December 2021. Based on eligibility, studies were selected, and quality appraised after which thematic analysis and narrative synthesis was conducted. Twenty-nine studies were included in the systematic review. Due to paucity and heterogeneity of quantitative studies, the review was limited to a thematic analysis. Adolescent and health provider perspectives alike underscored the burden and outcomes of mistreatment. Need for RMC interventions to improve quality of maternity care was recommended by majority of studies.